Aesthetic Understanding of Organizational Life - Strati, Antonio (Academy of Management Review, 1992)
The weak point of study of aesthetics in organizational life has been theorists' definition of the object of analysis, even before their use of methodology and techniques. This article takes a holistic approach to organizations in order to promote aesthetic awareness as a legitimate form of understanding organizational life. It is in contrast to previous approaches that treat the aesthetic dimension as one organizational theme among many. The article illustrates the elusiveness of the aesthetic dimension as an object of knowledge, and it also demonstrates the close link between the organizational aesthetic and the complex process of its deconstruction, comprehension, and communication.